(untitled) (Journal of Education and Development, 2021)
This theoretical and practical discussion intends to connect the formation of human capital of major Brazilian agents with investments in executive education based on demands from the areas of Corporate Governance and Tax. To this end, a literature review of the aforementioned themes was carried out, highlighting historical and contemporary aspects, relating them to the efforts of the companies studied: Petrobras, Braskem and OAS. In addition to the documentary research, semi-structured interviews were carried out with 22 executives from the aforementioned companies in order to reinforce knowledge about the phenomenon of governance, its consequences and consequences in shared services organizations. The text is structured in an introduction, discussion and theory segmented by study area and applied with notes from each business group and conclusions. The scientific contribution lies in strengthening the relationship between what is discussed in the academy and what is done in the market, intensifying the need for corporate education for business results.